HUBUNGAN PENGETAHUAN DAN SIKAP IBU RUMAH TANGGA DENGAN PERILAKU PENGGUNAAN BOTOL MINUMAN PLASTIK SEKALI PAKAI DI DUSUN SOCO KECAMATAN SALAMAN KABUPATEN MAGELANG - raras pinastiti; Surahma Asti Mulasari (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2021)
abstrac—Drinking water bottles are often being reused by people to be filled with refill drinking water, which has a high potential to cause cancer. Nearly 75% of women in Soco village, who are working as factory workers and traders, were often seen to use disposable mineral water bottles to place their water into. In other case, there were also women with different occupation who placed their daily drinking water stock in a disposable water bottles, and they often put them in a refrigerator. The purpose of this study was to determine the correlation of knowledge and the behavior of women/housewives in Soco village towards the usage of disposable water bottles as daily usage. Quantitative research with analytic survey methods, using cross sectional approach. The sample in this study amounted to 75 respondents. The sampling technique uses simple random sampling with research instrumentation. Data analysis using the Chi-Square test. The knowledge of women/housewives’s usage of disposable plastic drink bottles in Soco village is 56% good, and 44% are not good. Good attitude 77,3% and bad 22,7%. Good behavior 54,7% and bad 45,3%. The Chi-Square analysis showed that there was a correlations between the knowledge of housewives of Soco village and the behavior of disposable plastic drink bottles usage (p=0,034, RP=1,818 CI=1,093-3,023) and there was a correlation between women/housewives of Soco village’s attitudes with the behavior of the usage of disposable water bottles (p=0,008, RP=2,112 CI=1,372-3,252). There is a correlation between knowledge and the attitudes of women/housewives in Soco village and the behavior of disposable plastic bottles usage.